Resilience promotion of adolescents who live in poverty situation - Costa,Maria Isabelly (2020)
Abstract Introduction: Poverty is considered a worldwide phenomenon, of historical processes and social exclusion, being understood through a multidimensional perspective, that goes beyond income privation. Its definition is related to the society or the period in which it is included, being necessary the identification of which goods and services must be guaranteed. Objective: To analyze in literature resilience promotion in adolescents in poverty situation. Methods: Integrative review in literature, performed from December 2018 to February 2019 in databases LILACS, CINAHL, MEDLINE with the descriptors “resilience and poverty and vulnerable population”, published in the last six years. Results: Poverty is a vulnerability that enhances other vulnerabilities with implications as the alcohol and drugs consumption, violence, early start of sexual intercourses, pregnancy in adolescence, sexually transmitted infections, and social inequalities. Conclusions: Resilience promotion must be performed in all levels of life, once the experienced situations reverberate in the development process, being primordial strategies that promote even more their resilience, mainly in adolescence.